El laberinto del continuo - Asenjo, Florencio González (Sapientia, 2008)
It was Leibniz who coined the expression “The Labyrinth of the Continuum.” Nevertheless, he lacked the conceptual framework to adequately deal with this topic. Cantor’s Set Theory made it possible to solve the problem of the continuum in a satisfactorily from a conjunctionist perspective. But it was R. Dedekind who provided a better solution. Notwithstanding, the author asserts that Dedekind’s approach does not allow explaining all the aspects comprised in the continuum.